An Approach to Optimize Conversion Rate using Behavioral Economics - Dingre, Sneha Satish (Journal of Marketing Studies, 2024)
Purpose: This paper explores the integration of behavioral economics into the digital marketing landscape, emphasizing its potential to enhance conversion rates. Methodology: It highlights the significance of understanding human decision-making, incorporating behavioral elements into user profiles, and implementing a comprehensive conversion rate optimization framework. Findings: However, ethical considerations are crucial in this context, necessitating transparency, user autonomy, and responsible data handling to build enduring trust. Unique contributor to theory, policy and practice: As technology evolves, particularly with the rise of AI, establishing and reinforcing ethical guidelines becomes imperative for organizations to navigate the digital landscape with integrity and responsible behavioral economics practices.